Pengaruh Gaya Kepemimpinan Dan Displin Kerja Terhadap Kinerja Pegawai Dengan Motivasi Kerja Sebagai Variabel Intervening Pada UPTD Puskesmas Lubuk Alung - Ardila Febrianti; Marta Widian Sari; Yosi Puspita Sari (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to determine and analyze the influence of leadership style and work discipline on employee performance, both directly and indirectly through work motivation as an intervening variable at UPTD Puskesmas Lubuk Alung. This research employs a quantitative method with a causal associative approach. The population in this study were all employees of UPTD Puskesmas Lubuk Alung, totaling 55 people. Due to the small population size, the sampling technique used was saturated sampling (census), where the entire population was used as the sample. Data collection was conducted through surveys and the distribution of questionnaires using a Likert scale. The data analysis technique used was Structural Equation Modelling (SEM) based on Partial Least Square (PLS) with the assistance of SmartPLS 3.0 software.The results of this study indicate that: (1) Leadership style has a positive and significant effect on work motivation; (2) Work discipline has a positive and significant effect on work motivation; (3) Leadership style has a positive and significant direct effect on employee performance; (4) Work discipline has a positive but not significant direct effect on employee performance; (5) Work motivation has a positive and significant effect on employee performance; (6) Leadership style has a significant effect on employee performance through work motivation as an intervening variable; and (7) Work discipline has a significant effect on employee performance through work motivation as an intervening variable. These findings suggest that while discipline alone does not directly improve performance, it becomes effective when it successfully boosts employee motivation .